Quality of match for statistical matches used in the 1999 and 2005 LIMEW estimates for Canada - Thomas Masterson (Levy Economics Institute of Bard College, 2010)
The quality of match of four statistical matches used in the LIMEW estimates for Canada for 1999 and 2005 is described. The first match combines the 1999 Survey of Financial Security (SFS) with the 1999 Survey of Labour and Income Dynamics (SLID). The second match combines the 1998 General Social Survey (GSS) with the 1999 SLID. The third match combines the 2005 SFS with the 2005 SLID. The fourth match combines the 2005 GSS with the 2005 SLID. In each case, the alignment of the two datasets is examined, after which various aspects of the match quality are described. Also in each case, the matches are of high quality, given the nature of the source datasets.
Keywords: C14; C40; D31; 330; statistical matching; wealth distribution; time use; household production; Canada; LIMEW